COVID-19 drug research and the cohort multiple randomised controlled trial design. Issue 3 (15th September 2022) - Dal-Ré, Rafael
Soon after the start of the coronavirus disease 2019 (COVID-19) pandemic, in May 2020, more than 1300 trials were registered worldwide, 82% of which were devoted to assessing drugs or biologics [1]. Most of them were non-randomised trials or randomised controlled trials (RCTs). A few were adaptive, platform trials. However, in March 2020, the public hospitals of Paris (France) registered a cohort study, CORIMUNO-19 (NCT04324047), aiming to collect observational data to nest a series of RCTs to assess interventions for COVID-19 patients, i.e. a cohort multiple RCT (cmRCT). This clinical research approach has been exceptional in the COVID-19 pandemic. In the cohort multiple randomised controlled trial design, consent is not sought from control group participants in each trial conducted within the cohort, so it is ethically inappropriate for assessment of medicinal products in COVID-19 patients https://bit.ly/3xtBX3m